The Missing Link in the Covid-19 Vaccine Race. Issue 5 (4th May 2021) - Zizzo, John
ABSTRACT: Operation Warp Speed and global vaccine research efforts have succeeded in rapidly launching three vaccine candidates for coronavirus disease 2019 (COVID-19) into Phase III clinical trials. A recent letter from Centers for Disease Control and Prevention (CDC) Director Redfield underscored the possibility of "large-scale" distribution of a coronavirus vaccine as early as November 1, 2020. However, recent polling reveals that the majority of Americans remain skeptical of both the safety and efficacy of a potential Covid-19 vaccine. Even more troublesome is the fact that a comprehensive, collaborative vaccine marketing campaign has not been initiated to educate the U.S. public on and encourage widespread Covid-19 vaccination. Accordingly, this article lays out a plan of action, utilizing proven immunization marketing strategies and novel approaches, that could be used to combat vaccine hesitancy toward Covid-19. A vaccine may indeed be our ticket out of this pandemic, but targeted marketing is needed to increase public optimism toward that fact.